Current and Future Clinical Applications of ctDNA in Immuno-Oncology - Stadler, Julia-Christina; Belloum, Yassine; Deitert, Benjamin; Sementsov, Mark; Heidrich, Isabel; Gebhardt, Christoffer; Keller, Laura; Pantel, Klaus (Cancer research (Chicago, Ill.), 2022)
Testing peripheral blood for circulating tumor DNA (ctDNA) offers a minimally invasive opportunity to diagnose, characterize, and monitor the disease in individual cancer patients. ctDNA can reflect the actual tumor burden and specific genomic state of disease and thus might serve as a prognostic and predictive biomarker for immune checkpoint inhibitor (ICI) therapy. Recent studies in various cancer entities (e.g., melanoma, non–small cell lung cancer, colon cancer, and urothelial cancer) have shown that sequential ctDNA analyses allow for the identification of responders to ICI therapy, with a significant lead time to imaging. ctDNA assessment may also help distinguish pseudoprogression under ICI therapy from real progression. Developing dynamic changes in ctDNA concentrations as a potential surrogate endpoint of clinical efficacy in patients undergoing adjuvant immunotherapy is ongoing. Besides overall ctDNA burden, further ctDNA characterization can help uncover tumor-specific determinants (e.g., tumor mutational burden and microsatellite instability) of responses or resistance to immunotherapy. In future studies, standardized ctDNA assessments need to be included in interventional clinical trials across cancer entities to demonstrate the clinical utility of ctDNA as a biomarker for personalized cancer immunotherapy.